A survey of South African English verse printed in Cape periodicals and newspapers from 1824-1851 - Hammond, Carol Anne (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1972)
An interest in colonial literature is relatively new in the study of English. English-speaking South Africans especially, cut off as they are, a minority group in a new republic, have begun to re-assess their identity through a study of their existing literature. When asked what South African verse there was beside his own, Kipling remarked, "As to South African verse, it's a case of there's Pringle, and there's Pringle, and after that one must hunt the local papers." This thesis is the result of such a hunt - the hunt being limited to the years 1824 to 1851 - and on occasion, the writer has been tempted to conclude rather unfairly, "And there is only Pringle." It cannot be claimed that every poem ever printed during the period under review has been collected and examined, for the reason that many volumes of old newspapers are no longer available. Nevertheless, it has been possible to make a representative selection, which could provide the raw material for several theses to come. A detailed study of critical criteria prevalent at the Cape during this period, or public taste and the influence especially of the lesser British poets are some of the topics which might repay study. Intro., p. 1.
Keywords: Mass media and literature -- 19th century; South African poetry (English) -- History and criticism -- 19th century